Pembentukan Karangtaruna Desa Waijarang Sebagai Main Power Pemberdayaan Pemuda Oleh Mahasiswa KKNT-PPM Unwira 2022 - Adju, Lede; G. Suban Yunior, Andriano; Laga Waleng, Kornelius; Peni Bean, Yosefina; Alma Frida Paus, Agripina; Lobain, Ermilando; Rivaldiy Ganggut, Leonardus; Longa Pegan, Maria; Bay Koda, Charles; Rahaman Kadir, Eko; Adi Putra Amalo, Chrisleman; Jeferius Naya, Ulrikus; Don Bosko Manu, Frafilius; Edwin Tue P. Lejap , Gracianus (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2023)
Karangtaruna is a social organization that becomes the strength of young people in the village. Karangtaruna village by KKNT-PPM Unwira 2022 students is a community service that takes a special role in empowering village youth. The purpose of forming this Karang Taruna is a form of participation and concern for the problems faced by the village community. Activities carried out at the Waijarang Village Office, Nubatukan District, Lembata Regency provide many benefits. The benefits of youth activities, more specifically, must be a continuation of social groups with free creative space so that the planned and planned dynamic steps can be carried out properly. In addition, the formation of Karang Taruna has given a positive color in building the role of each young man and woman in preparing for this year's moment of independence